2003
DOI: 10.1093/jn/133.10.3153
|View full text |Cite
|
Sign up to set email alerts
|

Replacement-Fed Infants Born to HIV-Infected Mothers in India Have a High Early Postpartum Rate of Hospitalization

Abstract: Access to safe breast-feeding alternatives for HIV-infected mothers and their infants in many settings is limited. We compared the rates of early postpartum hospitalization of infants born to HIV-infected mothers using different infant-feeding practices in a large government hospital in Pune, India. From March 1, 2000 to November 30, 2001, infants born to HIV-infected mothers were followed in a postpartum clinic. All mothers had received a standard short course of antenatal zidovudine. Infant-feeding practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 10 publications
5
36
1
Order By: Relevance
“…It is, however, no longer recommended for feeding infants < 6 mo because of insufficient macro-and micronutrient content, concerns about the safety of storage, and occult bleeding that nonhuman milks can cause (7,57). Indeed, data from the main study of replacement feeding with nonformula modified animal milks indicated that Indian infants who were primarily fed modified animal milks had a greatly increased rate of hospital admission than those who were breastfed, mainly due to gastroenteritis with dehydration (58). In industrialized countries, replacement feeding has been AFASS for most HIV-positive women, and it is now standard practice for women there to feed their infants formula.…”
Section: Current Knowledge and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, no longer recommended for feeding infants < 6 mo because of insufficient macro-and micronutrient content, concerns about the safety of storage, and occult bleeding that nonhuman milks can cause (7,57). Indeed, data from the main study of replacement feeding with nonformula modified animal milks indicated that Indian infants who were primarily fed modified animal milks had a greatly increased rate of hospital admission than those who were breastfed, mainly due to gastroenteritis with dehydration (58). In industrialized countries, replacement feeding has been AFASS for most HIV-positive women, and it is now standard practice for women there to feed their infants formula.…”
Section: Current Knowledge and Recommendationsmentioning
confidence: 99%
“…Although the risk of HIV transmission continues for as long as breastfeeding continues (32), HIV-free survival of HIV-exposed infants who breastfed beyond 6 mo was similar to that of infants who received no breast milk after 6 mo (86,87). Infants given replacement foods after a period of breastfeeding also suffered increased serious infections, including diarrhea and pneumonia, growth faltering, and death (45)(46)(47)50,51,58). The importance placed on maximizing an infant's continued access to breast milk in the 2010 recommendations reflects the immunological benefits of breast milk as well as the importance of breast milk in providing adequate nutrition to infants > 6 mo of age.…”
Section: Current Knowledge and Recommendationsmentioning
confidence: 99%
“…These observations are similar to trends observed in the present study. [12] In a previous study conducted by Lunn [13] a much higher percentage of children were found to be overweight and obese (57.4%), with not much difference between boys and girls.…”
Section: Discussionmentioning
confidence: 90%
“…In a study conducted at SNDT Women's University in Mumbai, 7.7 percent of children aged 7 to 10 years were overweight and 13.2 percent were obese. [12] Phadke et al observed that a higher percentage of boys were overweight or obese compared to girls. These observations are similar to trends observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of breastfeeding eliminates the risk of HIV transmission, but is detrimental in terms of child survival. Increased infant morbidity and mortality associated with replacement feeds have been reported in several sub-Saharan African countries [18,[23][24][25][26]. Replacement feeding is the feeding of an infant who is receiving no breast milk but is given a diet that provides all the nutrients the infant needs until the age at which he/she can be fully fed with family foods.…”
Section: Introductionmentioning
confidence: 99%